Kadar Glukosa Darah Pada Pasien Covid-19 Lanjut Usia - Widyastuti, Rahma; Tunjung, Ellies Tunjung; Purwaningsih, Nur vita; Samsudin, Rinza Rahmawati (Universitas Muhammadiyah Surabaya, 2023)
COVID-19 (Coronaviruses Disease 2019) is a disease caused by a new type of corona virus, namely Sars-CoV-2, was first reported in Wuhan, China on December 31 2019. The death rate in elderly patients continues to increase, accounting for 21.9% . COVID-19 risk assessments show that assessing blood glucose levels has the potential to better identify people at risk of adverse outcomes. Blood sugar levels are affected by a number of factors, including gender and age. At this point, elderly patients experience many physical and mental changes, especially the decline in individual functions and abilities in general. This study aims to describe the results of examining blood glucose levels in elderly COVID-19 patients at Brawijaya Hospital, Surabaya. This type of research is descriptive research with secondary data from the laboratory using total sampling technique. The sample in this study were 65 elderly patients who tested positive for COVID-19 who had blood glucose checked at the clinical pathology laboratory in the September- December 2020 period at Brawijaya Hospital, Surabaya. Variables are then grouped and then tabulated and displayed descriptively in percentage form. The results of this study were obtained from 65 elderly COVID-19 patients who had normal fasting blood glucose levels (<100 mg/dl) which was 6.15%, while those who had abnormal glucose levels (>100 mg/dl) were 93.85%. . These results indicate that the majority of elderly COVID-19 patients have abnormal blood glucose levels